In vitro antifungal activities of some mushroom extracts against yeast isolates among women with vulvovaginal candidiasis in a teaching hospital - Adewale Oke; Olayinka Oluranti; Gbemisola Idowu (Babcock University Medical Journal)
Objective: Vulvovaginal candidiasis is a common fungal opportunist infection of the female genital parts caused by Candida species. Although it is usually mild, severe cases leading to complications do occur. Studies on natural therapy against candidiasis are rare. Hence, this study was aimed at evaluating the antifungal potentials of Ganoderma applanatum, Ganoderma lucidum, Pleurotus and Polyporus mushrooms against Candida species isolated from vaginal specimens.